2016
DOI: 10.3390/nu8120791
|View full text |Cite
|
Sign up to set email alerts
|

Xylobiose, an Alternative Sweetener, Ameliorates Diabetes-Related Metabolic Changes by Regulating Hepatic Lipogenesis and miR-122a/33a in db/db Mice

Abstract: Type 2 diabetes is a major public health concern worldwide. Xylobiose (XB) consists of two molecules of d-xylose and is a major disaccharide in xylooligosaccharides that are used as prebiotics. We hypothesized that XB could regulate diabetes-related metabolic and genetic changes via microRNA expression in db/db mice. For six weeks, C57BL/KsJ-db/db mice received 5% XB as part of the total sucrose content of their diet. XB supplementation improved glucose tolerance with reduced levels of OGTT AUC, fasting blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 65 publications
3
24
0
Order By: Relevance
“…Accumulating research has indicated that miRNAs play a central role in muscle development and disease [ 36 ]. It has been reported that exogenous nutrients (resveratrol and xylobiose) can modulate physiological functions by altering the miRNA expression profile [ 37 , 38 ]. Prompted by these findings, we explored whether miRNAs play an important role in GAA-induced myogenic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating research has indicated that miRNAs play a central role in muscle development and disease [ 36 ]. It has been reported that exogenous nutrients (resveratrol and xylobiose) can modulate physiological functions by altering the miRNA expression profile [ 37 , 38 ]. Prompted by these findings, we explored whether miRNAs play an important role in GAA-induced myogenic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Acting as an integration point for multiple biochemical signals, MAPK participates in a wide variety of cellular processes such as proliferation, differentiation and apoptosis [54-56]. The p38 MAPK pathway is known to play an important role in podocyte apoptosis [33, 57]. Adhikary et al [58] reported that greater numbers of phosphorylated p38 cells were observed in the kidney of diabetic patients by immunohistochemistry compared with those in normal humans, indicating that increased p38 MAPK signaling is a feature of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma insulin concentration was measured using an ultrasensitive mouse insulin ELISA kit (Crystal Chem., Inc., Downers Grove, IL, USA). The homeostasis model assessment of insulin resistance (HOMA‐IR) was calculated according to the following formula: HOMA‐IR = [fasting plasma insulin (ng·mL −1 ) × fasting glucose (mg·100 mL −1 )]/22.5 (Lim et al ., ).…”
Section: Methodsmentioning
confidence: 97%